The Role of Teachers’ Professional Ethics in Supporting Teacher Professionalism: A Literature Review - Asqoliyah, Asqoliyah; Elsa Merinda Isabela Mote; Ali Fikri; Listya Almara; Rini Sri Handayani; Ratna Dewi; Dewi Robiatun Muharomah (The Future of Education Journal, 2026)
Indonesian education is facing a moral decline among students, marked by increasing cases of bullying, declining responsibility, low honesty, and weakening respect for teachers and the school environment. This condition underscores the urgency of teachers’ professional ethics as a fundamental moral foundation to support professionalism in the digital era. This qualitative descriptive literature study examines the role of teachers’ professional ethics in enhancing professionalism through the analysis of 25 purposively selected sources (2021–2025) from Google Scholar, Scopus, and national repositories. Data were analyzed using thematic content analysis and NVivo coding, with source triangulation employed to ensure validity. The findings indicate that professional ethics guide responsible, honest, and fair attitudes that, when integrated with pedagogical competence, improve instructional quality and foster students’ character development. Continuous ethics training through case-based workshops and institutional support is recommended to promote integrity-driven educational practices.